The slope of a line that is perpendicular to a line whose equation is −2y = 3x + 7 is
Solution:
Given that we have to find the slope of the line that is perpendicular to a line whose equation is −2y = 3x + 7
The slope intercept form is given as:
y = mx + c
Where "m" is the slope of line and "c" is the y - intercept
Given equation is:
On comparing the above equation with slope intercept form,
We know that product of slope of a line and slope of line perpendicular to it is -1
Therefore,
Thus slope of line that is perpendicular to given line is
70
120
140
Answer:
D is the correct answer.
Step-by-step explanation:
Answer:
Option 4
Step-by-step explanation:
It's a geometric progression.
After t years,
500(1.1^t)
After 6 years,
500(1.1⁶) = 885.7805
B. 405
C. 1,215
The fifth term of a sequence whose first term is 5 and whose common ratio is 3 will be 405. Then the correct option is B.
A series of non-zero integers where every term after the first is obtained by increasing the one before it by a constant, non-zero value known as the scale factor.
Let a₁ be the first term and r be the common ratio.
Then the nth term of the geometric sequence is given as,
aₙ = a₁ · (r)ⁿ⁻¹
The first term is 5 and its common ratio is 3. Then the formula is given as,
aₙ = 5 · (3)ⁿ⁻¹
The fifth term of a sequence will be given as,
a₅ = 5 · (3)⁵⁻¹
a₅ = 5 · (3)⁴
a₅ = 5 · 81
a₅ = 405
The fifth term of a sequence whose first term is 5 and whose common ratio is 3 will be 405. Then the correct option is B.
More about the geometric sequence link is given below.
#SPJ2
explanation would be lit
When two the same numbers under the square root multiply, they are equal to the value under the square root, for example √2⋅√2 = 2. So then we have:
3√2⋅2√8⋅√3⋅√6 = 3⋅√2⋅2⋅√(2⋅2⋅2)⋅√3⋅√(3⋅2) = 3⋅2⋅√2⋅√2⋅√2⋅√2⋅√2⋅√3⋅√3 = 3⋅2⋅2⋅√2⋅3 = 36⋅√2
or if the bolded 2 from above is also the square root, then the solution is:
3√(2⋅2)√(2⋅2⋅2)⋅√3⋅√(3⋅2) = 54
Answer:
72√2
Step-by-step explanation:
simplify all of the radicals into their factors, then pull out integers. If you do this, only √2 remains. Then, multiply all the integers.
Answer
f^-1(x) =√[(3-x)÷3]
Step-by-step explanation:
y=-3x^2+3
interchange 'y' with 'x'
x=-3y^2+3
make y the subject
3y^2=3-x
divide by '3' both sides
y^2=(3-x)÷3
apply square root both sides
√(y^2)=√[(3-x)÷3]
y=√[(3-x)÷3]
f^-1(x) =√[(3-x)÷3]
the inverse of the given function is
f^-1(x)=√[(3-x)÷3]